PERAN KYAI DALAM MENANAMKAN NILAI KEJUJURAN DI PONDOK PESANTREN DARUL ILMI PUTRI KOTA BANJARBARU - Fatimah Fatimah; Muhamad Ramli (ADDABANA: Jurnal Pendidikan Agama Islam, 2019)
This study discusses the role of kyai in instilling the value of honesty in boarding schools Darul Ilmi Daughter Banjarbaru. Formulation of the problem in this research is how Patni's role in instilling values honesty in boarding schools Darul Ilmi Daughter Banjarbaru and any factors that support and slow him down. Based on the formulation of the problem, then the purpose of this research is to find out how Patni's role in instilling the value of honesty as well as any factors that support and that slow him down. The subject in this study are kyai, ustadzah, as well as students of Princess mualimat. Whereas the object of this research is in Kyai role in instilling the values of honesty and what factors that influence the cultivation of value honesty in boarding schools Darul Ilmi's daughter. The author uses data mining engineering interview, observation, and documentation. While the engineering management and data are done by editing and data classification, and interpretation of data further analyzed as well as qualitative and deskriktif conclusion inductive way. Based on the results of the study, noted that the role of kyai in instilling the value of honesty in boarding schools Darul Ilmi Daughter through education religious education and example. As for the example: education as the supervisor, controller, educators for any act or behavior of students. In addition kyai also had a role as a leader in the teaching and learning process, corrector, inspirator, motivator and as a model for the a santri especially in the values of honesty, because honesty is a virtue, morals which will take on a very important impact in the life of the individual and of society. While the role of religious education in the Kyai, namely: Ta'limul of the book and may. As for the supporting factors, namely: the ma'had religious activities, supporting the code of conduct, while restricting factor: the number of students that are heterogeneous, and the outside environment. Keywords: Kiai Pesantren, Planting, Values, Honesty.